JSSS 2021
DOI: 10.20517/jsss.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

A security study of Bluetooth-powered robot toy

Abstract: Aim: A smart toy robot has its intellect with circuits on board. It has a built-in microprocessor, sensors of one or more types, a mechanical system including moving parts, and some firmware to control and tie the parts together. The embedded sensors and devices help to create their functionality. These devices include wireless communication for data transfer. One such device for wireless communication is Bluetooth, which can be dangerous due to attack vulnerabilities, especially on Bluetooth Low Energy (BLE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(1) Camera Calibration and Data Transmission Module. The camera is calibrated by collecting a certain amount of images with a complete identification map, and the internal parameters of the camera are calculated, and the internal parameters of the calculation are stored in an XML format file [20]. By reading the calculated internal parameters, based on each frame of image collected, the external parameters of the camera are calculated, and the calculated external parameters of the camera and the collected current frame image data are sent to the server.…”
Section: Division and Design Of System Functional Modulesmentioning
confidence: 99%
“…(1) Camera Calibration and Data Transmission Module. The camera is calibrated by collecting a certain amount of images with a complete identification map, and the internal parameters of the camera are calculated, and the internal parameters of the calculation are stored in an XML format file [20]. By reading the calculated internal parameters, based on each frame of image collected, the external parameters of the camera are calculated, and the calculated external parameters of the camera and the collected current frame image data are sent to the server.…”
Section: Division and Design Of System Functional Modulesmentioning
confidence: 99%
“…Research development has evolved from hypermediabased adaptive learning systems to mobile learning and ubiquitous learning environments, and researchers have focused on learning environments that mainly provide the right content for the right learners at the right time and place, but this is only a small part of the learning experience for learners to personalize their learning, ignoring the interactions and scenarios in the learning environment. Current adaptive learning technologies mainly focus on personalized recommendation of learning resources, learning path referral, and precise positioning of learning content as the main research hotspots, such as adaptive learning environments [14]. Researchers gradually found that learners' learning styles dominate the adaptive learning environment [15].…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…The design and development of augmented reality teaching resources not only helps to create and control teaching and learning situations but also engages the multiple senses of students, allowing learners to escape the dull monotony of written language and receive stimuli efficiently [9]. It has wide application prospects in scenario creation, learning mode innovation, interactive design, expanding learning space, and conducting classroom activities [10]. At this stage, there are fewer studies on augmented reality teaching resources for primary school English in China.…”
Section: Current Status Of Researchmentioning
confidence: 99%